2003
DOI: 10.1037/0278-7393.29.6.1381
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Mediation or Absence of Mediation? Commentary on Crutcher and Ericsson (2000).

Abstract: R. J. Crutcher and K. A. Ericsson (2000; see record 2000-05419-014) showed that subjects stopped reporting mnemonic mediation in a recall task after sufficient practice. They concluded that subjects continued to use the mediator indefinitely but that its execution eventually became automatic and no longer required access to working memory. Their article thus supports the more general hypothesis that multistep cognition can take place without awareness. In this article the authors evaluate that conclusion on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 18 publications
(33 reference statements)
3
25
1
Order By: Relevance
“…Third, a shift from mediated to direct retrieval during practice predicted better word retention over time: words that were retrieved directly, without mediators during practice were more likely to be recalled correctly on a test one week after practice. This is in line with suggestions that direct memory associations can be reactivated more easily, because fewer interim steps are needed and thus the chance for activation of competing, irrelevant information is lower (Lehman et al, 2014;McElree, 2001;Rickard & Bajic, 2003). The present data did not show a relation between the moment of shift during practice and word retention, however.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Third, a shift from mediated to direct retrieval during practice predicted better word retention over time: words that were retrieved directly, without mediators during practice were more likely to be recalled correctly on a test one week after practice. This is in line with suggestions that direct memory associations can be reactivated more easily, because fewer interim steps are needed and thus the chance for activation of competing, irrelevant information is lower (Lehman et al, 2014;McElree, 2001;Rickard & Bajic, 2003). The present data did not show a relation between the moment of shift during practice and word retention, however.…”
Section: Discussionsupporting
confidence: 92%
“…The main focus in prior research has been on the effects of the keyword method on recall accuracy, both during practice and on later performance tests (e.g., Adams & McIntyre, 1967;Atkinson, 1975;Atkinson & Raugh, 1975;Fritz et al, 2007;Rickard & Bajic, 2003, 2006. The present study taps more directly into the mental processes during word learning with keyword mediators.…”
Section: Present Studymentioning
confidence: 96%
See 2 more Smart Citations
“…As this retrieval-induced interference effect had previously been shown to be induced by number-fact retrieval practice but not by practice of arithmetic procedures (Campbell & Therriault, 2013), Campbell et al suggested that the arithmetically superior Chinese participants might solve small addition problems by fast procedures whereas the Canadians used number-fact retrieval. Despite these seemingly converging sources of evidence for fast addition procedures, there appears to be little evidence outside of the addition domain to support the idea that mediational strategies for associative learning become proceduralized with practice (see, e.g., Kole & Healy, 2013;Rickard & Bajic, 2003). Furthermore, as we discuss next, repeated attempts have failed to demonstrate a basic behavioral prediction of counting procedures for simple addition.…”
mentioning
confidence: 95%